More than health: quality of life trajectories among older adultsfindings from The Irish Longitudinal Study of Ageing (TILDA) - Ward, Mark (My University, 2019)
Purpose: To test whether ill-health is associated with a decrease in quality of life (QoL) over time and if positive social circumstances are beneficial to QoL, using the shorter form CASP-12 in a sample drawn from a nationally representative cohort of older adults. To do so, the association between factors from a number of life domains and QoL was investigated. Methods: Data were from the first three waves of The Irish Longitudinal Study on Ageing, a prospective nationally representative study of community dwelling older adults in the Republic of Ireland. QoL was measured using the shorter form CASP-12 and the latent growth curve method was used to describe within- and between-person variation in longitudinal QoL trajectories. Results: There was considerable variation in QoL scores cross-sectionally and longitudinally. QoL did not decline linearly with age but increased from age 50 and peaked at 68 years before declining in older age. QoL differed significantly between individuals and decreased over time. A variety of demographic, health, and social characteristics were associated with changes in QoL over time. These included cohabiting; self-rated health; functional limitations; fear of falling; mental health; loneliness; social networks; social activities; caring for grandchildren; income; and death of a spouse. Conclusions: Changes in QoL over time were not merely a function of ageing, or declining health but resulted from factors from a variety of domains with loneliness and social participation particularly important. Policies concerned with successful ageing and QoL among older adults must consider social circumstances as well as physical and psychological well-being.
PUBLISHED
Keywords: Quality of life; CASP-12; Older age; Latent growth curve model; Ageing